InSAR monitoring of ground deformation due to CO2 injection at an enhanced oil recovery site, West Texas. (October 2015) - Yang, Qian; Zhao, Wenliang; Dixon, Timothy H.; Amelung, Falk; Han, Weon Shik; Li, Peng
Highlights: InSAR data show surface uplift up to 10 cm at a CO2 -EOR site in West Texas between January 2007 and March 2011. Our simulations show up to 10 MPa pressure buildup in the reservoir over four years of net injection and production. The observed surface uplift was mainly caused by CO2 injection. Abstract: Interferometric synthetic aperture radar (InSAR) measurements have been used to measure ground deformation associated with fluid injection/production at an enhanced oil recovery (EOR) field in Scurry County, West Texas. 100 million tons (Mt) of supercritical CO2 have been sequestered here since 1972, of which about half has been sequestered since 2004. InSAR data show surface uplift up to 10 cm in the field between January 2007 and March 2011. We evaluated data concerning injection and production of CO2, water, oil and hydrocarbon gas from 2004 to 2011 to investigate causes of the observed uplift. An analytical model is used to calculate reservoir pressure change and surface displacement. Our simulations show up to 10 MPa pressure buildup in the reservoir over four years of net injection and production. Surface displacement predictions agree well with the InSAR observations. Water injection alone cannot explain the 2007–2011 surface uplift because the net injected water (∼1 Mt) is negligible compared to the net injected CO2 (∼24 Mt). The predicted total pressure buildup (up to 10 MPa) consists of net CO2 injection (up to 12 MPa), net water injection (up to 2 MPa), and oil and gas production (up to −0.4 MPa). Hence, observed ground uplift was mainly caused by CO2 injection.